2019
DOI: 10.1371/journal.pone.0211759
|View full text |Cite
|
Sign up to set email alerts
|

Access to and price trends of antidiabetic, antihypertensive, and antilipidemic drugs in outpatient settings of the Universal Coverage Scheme in Thailand

Abstract: Under the Universal Coverage Scheme (UCS) with payment per capita for outpatient (OP) services, hospitals’ financial risks will rise if access to essential drugs increases. This study examined trends in access to and price of essential drugs for noncommunicable diseases (NCDs) and an overall purchasing price index (PPI) for an OP drug basket from public hospitals. To examine drug access, OP prescription data from 2010–2012 were obtained from the UCS. Access to thirteen drugs for diabetes, hypertension, and dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Effects of centralised negotiation or other regulation approaches on curbing medication prices have been described in China 8 and other countries. [8][9][10][11] Previous studies have also shown that insurance coverage of medications without price negotiation led to a rise in medication use volumes as well as expenditures. 12 13 Expectations are that China's combined price negotiation and mandatory reimbursement policies decrease procurement cost per medication unit and increase utilisation and thereby improve access to and affordability of expensive targeted anticancer medications.…”
Section: What Do the New Findings Imply?mentioning
confidence: 99%
“…Effects of centralised negotiation or other regulation approaches on curbing medication prices have been described in China 8 and other countries. [8][9][10][11] Previous studies have also shown that insurance coverage of medications without price negotiation led to a rise in medication use volumes as well as expenditures. 12 13 Expectations are that China's combined price negotiation and mandatory reimbursement policies decrease procurement cost per medication unit and increase utilisation and thereby improve access to and affordability of expensive targeted anticancer medications.…”
Section: What Do the New Findings Imply?mentioning
confidence: 99%
“…The drug cost for NCDs accounts for a large proportion of all medical costs, and this situation is expected to continue for a long time. However, current studies on NCDs' medical expenses both at home and abroad still focus on the factors influencing NCDs' hospitalization expenses, forecasts of hospitalization expenses, or the composition of costs [14,15]. At the same time, there are few studies on outpatient expenses [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…This study proposes that the bargaining form of national health insurance drug negotiation (Limwattananon & Waleekhachonloet, 2019 ) can be used to bargain for the material suppliers or constructors involved in the renovation project in response to the problem of significant total investment and long payback period for the renovation of this project. The basic idea behind this strategy is to leverage a bigger market in return for a specialized negotiating zone, lowering individual costs.…”
Section: Discussionmentioning
confidence: 99%